Practical Implementation of Sustainability Accounting: A Research of Major Public Listed Companies: Array - Gachie, Wanjiru (The Journal of Accounting and Management, 2021)
This research proposes the integration of social and environmental pillars into existing economic pillar towards modernizing mainstream financial accounting in line with 21st-century diverse stakeholders’ sustainability needs. The identified research gap observes that 19th-century accounting no longer reflects an all-encompassing stakeholders’ interest. Hence in this 2020 decade transforming the basis of accounting and reporting is a fundamental concern. This research thus provides an opportunity rarely considered for an all-inclusive sustainability accounting evoking a shift in accounting fundamentals, principles, standards and frameworks for stakeholders’ holistic decision-making on enterprises going concern. The methodological approach adopted is an in-depth examination of two selected public listed companies’ annual financial statements during the last three years to provide insights on their integration of social and environmental into financial statements . Both literature and this research findings reveal low degree of commitment towards social and environmental sustainability in favor of economic activities mandated for listed companies. This validates formerly, now updated New Framework for seamless standardized assimilation of all three pillars in financial accounting. The practical implications contained in this research recommends a Framework for transitioning into a more-inclusive 21st-century sustainability accounting. The practical value contributes in transformation in accounting fundamentals to reflect updated stakeholders’ motivation.